2022
DOI: 10.3389/fmars.2022.1006432
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution variability of dissolved and suspended organic matter in the Cape Verde Frontal Zone

Abstract: Distributions of dissolved (DOM) and suspended (POM) organic matter, and their chromophoric (CDOM) and fluorescent (FDOM) fractions, are investigated at high resolution (< 10 km) in the Cape Verde Frontal Zone (CVFZ) during fall 2017. In the epipelagic layer (< 200 m), meso- and submesoscale structures (meanders, eddies) captured by the high resolution sampling dictate the tight coupling between physical and biogeochemical parameters at the front. Remarkably, fluorescent humic-like substances sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Therefore, Saharan dust might have attenuated UV exposure during cruise M156, limiting the photodegradation of humic‐like FDOM (Herman et al., 1999; Smyth, 2011). Moreover, Saharan dust can also be a source of humic‐like FDOM, especially of FDOM peak M (C398) (Campanero et al., 2022; Sánchez‐Pérez et al., 2016) and iron contained in dust and associated with humic substances might also attenuate photodegradation in surface waters (Y. H. Xiao et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Saharan dust might have attenuated UV exposure during cruise M156, limiting the photodegradation of humic‐like FDOM (Herman et al., 1999; Smyth, 2011). Moreover, Saharan dust can also be a source of humic‐like FDOM, especially of FDOM peak M (C398) (Campanero et al., 2022; Sánchez‐Pérez et al., 2016) and iron contained in dust and associated with humic substances might also attenuate photodegradation in surface waters (Y. H. Xiao et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The CBGF transports large amounts of coastal dissolved (DOM) and suspended organic matter (POM) originated in the Mauritanian coast to the adjacent oligotrophic open ocean (Gabric et al, 1993;Ohde et al, 2015). In surface and central waters, the distribution of DOM and POM is dictated by the position of the CVF and associated meanders and eddies (A ́lvarez- Salgado and Arıśtegui, 2015;Campanero et al, 2022;Valiente et al, 2022). In intermediate and deep waters, POM and DOM distribute according to water mass mixing and large-scale remineralization of these materials from the water mass formation areas to the CVFZ (Campanero et al, 2022;Valiente et al, 2022).…”
Section: Study Areamentioning
confidence: 99%
“…In surface and central waters, the distribution of DOM and POM is dictated by the position of the CVF and associated meanders and eddies (A ́lvarez- Salgado and Arıśtegui, 2015;Campanero et al, 2022;Valiente et al, 2022). In intermediate and deep waters, POM and DOM distribute according to water mass mixing and large-scale remineralization of these materials from the water mass formation areas to the CVFZ (Campanero et al, 2022;Valiente et al, 2022). The organic matter that is mineralized in the intermediate and deep layers of the CVFZ is primarily sinking POM, which is less susceptible to lateral transport in the surface layer, so it sinks fast into the deeper layer (Fischer et al, 2009;A ́lvarez-Salgado and Arıśtegui, 2015;Campanero et al, 2022;Valiente et al, 2022).…”
Section: Study Areamentioning
confidence: 99%
“…Due to the vertical motion associated with submesoscale processes, momentum and tracers such as heat, mass, oxygen, pollutants and carbon can be exchanged between the surface and the deep pycnocline (Smith et al, 2016;Erickson and Thompson, 2018;Su et al, 2018;Archer et al, 2020;Freilich and Mahadevan, 2021). Existing observational evidence and numerical studies indicate that submesoscale processes such as fronts and filaments can play an important role in ocean productivity, biogeochemical fluxes and biodiversity patterns (Mahadevan, 2016;Pascual et al, 2017;Lehahn et al, 2018;Hernańdez-Hernańdez et al, 2020;Fadeev et al, 2021;Kaiser et al, 2021;Campanero et al, 2022;Xiu et al, 2022). Based on an idealized modeling study, Levy and Martin (2013) demonstrated that the primary production associated with mesoscale currents can be underestimated by a third if submesoscale processes are not included.…”
Section: Introductionmentioning
confidence: 99%